HEALTH HISTORY FOR SAFE EXERCISE (Fiep Bulletin - online, 2025)
Introduction: Low levels of physical activity can cause recurring problems that affect health, interfering with the planning and practice of physical exercise. Objective: To identify the frequency of illnesses and/or health-related problems among university students taking the Physical Education course at UFPI to discuss aspects related to the safe practice of physical exercise Methods: The research was approved by the Research Ethics Committee of the Federal University of Piauí (opinion no. 6,709,601) and was developed using two instruments: a form about health history, and the International Physical Activity Questionnaire (IPAQ), which were applied in person to students from the 2nd to the 8th period, enrolled in the course in the academic semester 2024.1 Results: It was possible to identify the prevalence of 60% of male students, and 40% of female students, with an average age of 21.50 (±3.50) years. The frequency of osteomyoarticular dysfunctions was verified (49%); surgery or recommendation for surgery (23%); allergy or skin problems (19%); gastrointestinal problems (14%); and regular use of medication (13%), as health complications that are related to and influence the safe practice of physical exercise. Students also demonstrated a high prevalence of physical activity, classified as Active and Very Active. Conclusion: It is observed that some clinical conditions found in this study can be aggravated by the practice of physical exercise, therefore, Physical Education teachers must know the possible complications of these health conditions in order to prescribe and plan PE in a more assertive and safe way. be carried o
Keywords: Physical Education; Physical Activity; Health